2015
DOI: 10.1038/bjc.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Combination of microsatellite instability and BRAF mutation status for subtyping colorectal cancer

Abstract: Background:The objective of the study was to examine the role of microsatellite instability (MSI) and BRAFV600Emutation in colorectal cancer (CRC) by categorising patients into more detailed subtypes based on tumour characteristics.Methods:Tumour samples from 762 population-based patients with sporadic CRC were analysed for MSI and BRAFV600E by immunohistochemistry. Patient survival was followed-up for a median of 5.2 years.Results:Compared with microsatellite stable (MSS) CRC, MSI was prognostic for better di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
121
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 50 publications
13
121
1
1
Order By: Relevance
“…The same finding is obtained in 15% of LS cases, which makes differentiation from sporadic CRCs difficult 101 . In such cases, the V600E mutation in v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) gene eliminates the possibility of LS 102 .…”
Section: Microsatellite Instabilitysupporting
confidence: 59%
“…The same finding is obtained in 15% of LS cases, which makes differentiation from sporadic CRCs difficult 101 . In such cases, the V600E mutation in v-Raf murine sarcoma viral oncogene homolog B1 (BRAF) gene eliminates the possibility of LS 102 .…”
Section: Microsatellite Instabilitysupporting
confidence: 59%
“…Given that there is increasing evidence the BRAFV600E mutant microsatellite stable tumours are a particularly poor prognostic group, [22][23][24][25][26][27][28] we attempted to further stratify mucinous MMRp tumours on the basis of BRAF status. Interestingly, and perhaps unexpectedly, we found similar 5-year survival rates for BRAF wild type (57%) and BRAFV600E mutant (51%) MMRp mucinous colorectal cancers (P = 0.610).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is lower than other cohorts previously reported in China (Table 4). In Western European countries [33][34][35][36][37][38][39][40][43][44], most studies demonstrated that the RAF mutation rate was over 10%. In the United States, only a few studies demonstrated a higher mutation rate of RAF [15][16][17]45].…”
Section: : Ras Raf and Msi Status Of Colorectal Cancermentioning
confidence: 99%
“…The frequency of RAF mutation in various countries is 3-8 times higher in colon cancer than in rectal cancer [23,44]. The ratio of involvement is almost 2-5 times on the right compared to the left [43]. Besides, BRAF has an obvious relationship with tumor position and sex, and is also associated with highgrade tumors, mucous adenocarcinoma, and lymph node metastases.…”
Section: : Ras Raf and Msi Status Of Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation